2014
DOI: 10.1111/sji.12179
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Blood‐Derived Mesenchymal Stromal Cells Display a Novel Interaction between P‐Selectin and Galectin‐1

Abstract: Human multipotent mesenchymal stromal/stem cells (MSCs) have been shown to exert immunomodulatory properties that have great potential in therapies for various inflammatory and autoimmune disorders. However, intravenous delivery of these cells is followed by massive cell entrapment in the lungs and insufficient homing to target tissues or organs. In targeting to tissues, MSCs and other therapeutic cells employ similar mechanisms as leucocytes, including a cascade of rolling and adhesion steps mediated by selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…However, as MSCs do not express PSGL-1, they must use a different ligand to interact with P-selectin. One study has identified galectin-1 as one such candidate (Suila et al., 2014). Another study has identified CD24 as a potential P-selectin ligand in adipose tissue-derived stromal cells, which resemble MSCs (Bailey et al., 2009).…”
Section: Msc Homing Mechanismsmentioning
confidence: 99%
“…However, as MSCs do not express PSGL-1, they must use a different ligand to interact with P-selectin. One study has identified galectin-1 as one such candidate (Suila et al., 2014). Another study has identified CD24 as a potential P-selectin ligand in adipose tissue-derived stromal cells, which resemble MSCs (Bailey et al., 2009).…”
Section: Msc Homing Mechanismsmentioning
confidence: 99%
“…). Indeed, MSCs have been shown to express glycoproteins and galectin‐1 , which may represent alternative P‐selectin ligands. Furthermore, interaction of MSCs with P‐selectin might be mediated by a bridging mechanism involving platelets.…”
Section: Priming and Requirements For Extravasationmentioning
confidence: 99%
“…However, as most understanding of migration and homing mechanisms derived from studies evaluating leucocytes migrating into inflamed tissues, the fact that MSCs do not express the hematopoietic cell E-/L-selectin ligand (HCELL) [135], a specialized glycoform of CD44 on the migrating cell, as well as the P-selectin glycoprotein ligand-1 (PSGL-1) [135], raises the question of which selectin exactly employed by MSCs. One study has identified galectin-1 [138] as one such candidate, and another study has identified CD24 as a potential P-selectin ligand [139]. Following the initiation of tethering step, activation step is facilitated typically by G protein-coupled chemokine receptors in response to inflammatory signals.…”
Section: Homing and Hemocompatibility Considerationmentioning
confidence: 99%